WTO accession issues - Rolf J. Langhammer; Matthias Lücke (The world economy, 1999)
For many applicant countries, accession to the WTO has been, and still is, a frustratingly slow process. In this paper, we discuss the substantial, contentious issues that are slowing down progress in accession negotiations. We contrast these with the benefits of WTO accession not only to the applicant countries, but also to the multilateral trading system as a whole and, hence, to current members. Against this background, we suggest a strategy to accelerate accession without diluting the ground rules of the multilateral trading system.
Keywords: 330; WTO accession; transition economies; state trading; anti-dumping duties; WTO-Regeln; Mitgliedschaft; Verhandlungen; Kosten-Nutzen-Analyse; Weltwirtschaftsordnung; Welt